2008
DOI: 10.2967/jnumed.108.055350
|View full text |Cite
|
Sign up to set email alerts
|

Optimal Detection of Sentinel Lymph Node Metastases by Intraoperative Radioactive Threshold and Molecular Analysis in Patients with Melanoma

Abstract: The aim of this study was to optimize a protocol for radioguided biopsy of the sentinel lymph node (SLN) in patients with melanoma. The protocol was based on a combination of ex vivo counting of the nodes detected intraoperatively and analysis of the harvested nodes by hematoxylin and eosin staining plus immunohistochemistry (conventional histopathology [PATH]) and by molecular biology (reverse-transcriptase polymerase chain reaction [RT-PCR]). Methods: A total of 124 patients with primary clinical stage I-II … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(12 citation statements)
references
References 37 publications
0
12
0
Order By: Relevance
“…A further five studies were excluded because they either had a missing intervention or control group, or the population of interest was not studied. After review, 15 articles were included in the qualitative synthesis ( Fig . ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…A further five studies were excluded because they either had a missing intervention or control group, or the population of interest was not studied. After review, 15 articles were included in the qualitative synthesis ( Fig . ).…”
Section: Resultsmentioning
confidence: 99%
“…Two cohort studies were excluded from the meta‐analysis after failing the NOS tool bias analysis for lack of comparability of groups. The remaining 13 studies (11 cohort studies and 2 RCTs) were found to be suitable for analysis ( Fig.…”
Section: Resultsmentioning
confidence: 99%
“…In other malignant tumors, such as breast cancer or melanoma where SLN biopsy is also widely applied, the lymphatic path is not always assessed, and it is usually not included in the resected specimen. 8,9 In tumors of the anal canal that exceed the dentate line though, the excision of the anoinguinal lymphatic path, which corresponds to the inguinal crease, is indicated because it carries a significant malignant cellular load, otherwise treated with local radiotherapy. 10 The springbok pattern puts on the map the aggregate of local metastasis in anal cancer and leads the surgeon to include the related lymphatic path in the inguinal SLN dissection.…”
Section: Figurementioning
confidence: 99%
“…Lymphatic mapping using radio colloid reveals ways unexpected of lymphatic drainage, it finds all the stations limph node at a greater risk of metastasis and for each of them, locates the sentinel lymph node; it also allows the identification and biopsy of the lymph nodes in-transit (the lymph nodes under the skin spots between the seat skin of the melanoma and the station lymph node Res Rev Insights, 2017 doi: 10.15761/RRI.1000105 main) [49,50]. With the new generation of large -field of view gamma cameras, SPECT/TC has been incorporated in the SLN procedure.…”
Section: Main Applications Of Lymphoscintigraphy In the Sentinel Lympmentioning
confidence: 99%